2018
DOI: 10.1083/jcb.201807108
|View full text |Cite
|
Sign up to set email alerts
|

Mapping 3D genome organization relative to nuclear compartments using TSA-Seq as a cytological ruler

Abstract: While nuclear compartmentalization is an essential feature of three-dimensional genome organization, no genomic method exists for measuring chromosome distances to defined nuclear structures. In this study, we describe TSA-Seq, a new mapping method capable of providing a "cytological ruler" for estimating mean chromosomal distances from nuclear speckles genome-wide and for predicting several Mbp chromosome trajectories between nuclear compartments without sophisticated computational modeling. Ensemble-averaged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
477
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 326 publications
(555 citation statements)
references
References 56 publications
57
477
0
Order By: Relevance
“…However, it is worth noting that Vian and colleagues have demonstrated that TADs can disappear upon cohesin degradation and reappear after rescue, even in the absence of transcription [32]. Similarly, previous reports suggested that the act of transcription can influence the 3D structure of the nucleus [27,[58][59][60]. Indeed, although the compartmentalization was not markedly altered (Fig 4) we observed a reduction in TAD boundary strength upon transcriptional inhibition ( Fig 5).…”
Section: Proper Tad and Genomic Compartment Formationsupporting
confidence: 81%
“…However, it is worth noting that Vian and colleagues have demonstrated that TADs can disappear upon cohesin degradation and reappear after rescue, even in the absence of transcription [32]. Similarly, previous reports suggested that the act of transcription can influence the 3D structure of the nucleus [27,[58][59][60]. Indeed, although the compartmentalization was not markedly altered (Fig 4) we observed a reduction in TAD boundary strength upon transcriptional inhibition ( Fig 5).…”
Section: Proper Tad and Genomic Compartment Formationsupporting
confidence: 81%
“…One possibility is that the enhancers are differentially associating with nuclear speckles. It has been shown that distance from nuclear speckles in the A compartment is independent of the nuclear lamina compartment axis and is correlated with superenhancers and H3K4me3, H3K9ac, and CTCF peaks (32) . Thus the compartment-independent relocalizations we identified may represent differences in nuclear speckle association.…”
Section: Discussionmentioning
confidence: 99%
“…1a. Our goal is to identify genome-wide spatial compartmentalization patterns of the chromosomes by integrating TSA-seq (Chen et al, 2018) and DamID (Guelen et al, 2008;Meuleman et al, 2013) data together with Hi-C. TSA-seq and DamID provide complementary information to measure distance and contact frequency between chromosome regions and subnuclear structures. The rationale of including Hi-C is that the pairwise genomic regions spatially interacting with each other more often than expected (from Hi-C) are more likely to share similar spatial compartmentalization patterns.…”
Section: Overview Of the Spin Methodsmentioning
confidence: 99%
“…In this implementation of SPIN to infer genome-wide nuclear compartmentalization patterns, we used TSA-seq and DamID mapping data in K562 for nuclear speckles (TSA-Seq), lamina (DamID and TSA-Seq), and nucleoli (DamID). Nucleoli DamID data, generated using a Dam methylase fusion with a nucleolar targeting peptide repeat (4xAP3 (Scott et al, 2010)) is new; all remaining data are as published previously (Chen et al, 2018;Leemans et al, 2019). Details of the new nucleolar DamID mapping are described elsewhere (van Schaik et al manuscript in prep.).…”
Section: Spin Identifies Genome-wide Patterns Of Nuclear Compartmentamentioning
confidence: 99%
See 1 more Smart Citation